2022
DOI: 10.1038/s41598-022-21484-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of common and rare variants in multiplex multiple sclerosis families reveals an increased burden of common risk variation

Abstract: Many multiple sclerosis (MS)-associated common risk variants as well as candidate low-frequency and rare variants have been identified; however, approximately half of MS heritability remains unexplained. We studied seven multiplex MS families, six of which with parental consanguinity, to identify genetic factors that increase MS risk. Candidate genomic regions were identified through linkage analysis and homozygosity mapping, and fully penetrant, rare, and low-frequency variants were detected by exome sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A limitation of these previous studies was that they were conducted prior to the latest MS GWAS and thus used fewer MS risk variants to compute their polygenic risk scores. Recent work in a Turkish cohort has suggested that population-based MS cases have a higher PRS than people with MS from multicase families; however, this comparison was not statistically significant, and not all HLA risk alleles were able to be imputed [32]. These conflicting results also reflect the heterogeneity of common genetic risk profiles for MS.…”
Section: Discussionmentioning
confidence: 90%
“…A limitation of these previous studies was that they were conducted prior to the latest MS GWAS and thus used fewer MS risk variants to compute their polygenic risk scores. Recent work in a Turkish cohort has suggested that population-based MS cases have a higher PRS than people with MS from multicase families; however, this comparison was not statistically significant, and not all HLA risk alleles were able to be imputed [32]. These conflicting results also reflect the heterogeneity of common genetic risk profiles for MS.…”
Section: Discussionmentioning
confidence: 90%
“…It is possible that PC could reinforce several gene loci associated with MS (39). In a study by Everest et al, FMS cases were signi cantly more likely to experience common rare risk variation than controls and control families (41).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high prevalence of consanguinity among Emirati individuals, no significant differences in clinical and demographic characteristics were observed between those with familial and sporadic MS [ 42 ]. Previous studies have identified certain rare genetic risk variants that contribute to the heritability of MS, possibly explaining its occurrence in specific families [ 20 , 43 ], along with some hormonal contributors [ 44 ]. In contrast, additional studies have demonstrated a significant link between environmental factors and the development of MS, such as sunlight exposure, cigarette smoking, measles infection, Epstein-Barr virus (EBV) infection, and stressful events [ [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 99%